2019
DOI: 10.4103/ija.ija_315_19
|View full text |Cite
|
Sign up to set email alerts
|

Scalp block for analgesia after craniotomy: A meta-analysis

Abstract: Background and Aims:A previous meta-analysis reported that scalp block had limited benefits (low-quality evidence) compared to no-scalp block modalities for analgesia after craniotomy. However, it included studies using two different pain intensity measurement scales. Therefore, we performed another meta-analysis using a single scale.Methods:We conducted the search for all randomised controlled trials evaluating the effect of scalp block on postcraniotomy pain compared to no-scalp block in Cochrane Central Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 18 publications
2
20
0
2
Order By: Relevance
“…[ 8 ] Local anaesthesia infiltration is the cornerstone to blunt the noxious stimuli of skull pin insertion, and is typically provided by means of a scalp block, which when performed well with agents such as bupivacaine, levobupivacaine or ropivacaine can provide good and safe analgesia for 8 h or longer. [ 9 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Local anaesthesia infiltration is the cornerstone to blunt the noxious stimuli of skull pin insertion, and is typically provided by means of a scalp block, which when performed well with agents such as bupivacaine, levobupivacaine or ropivacaine can provide good and safe analgesia for 8 h or longer. [ 9 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvants like opioids, dexmedetomidine 12 , dexamethasone and magnesium sulphate 13 have been investigated by different investigators for their effect on the improvement of the quality and duration of the block with varying results. Meta-analysis of different randomised control studies (RCTs) have demonstrated a consistent reduction of pain severity 14 , which extends 6 hours after craniotomy 15 . A moderate reduction in opioid consumption in the 24 hours following craniotomy is also observed 16 .…”
Section: Scalp Blockmentioning
confidence: 99%
“…A moderate reduction in opioid consumption in the 24 hours following craniotomy is also observed 16 . Additionally, it reduces the incidences of postoperative nausea and vomiting, which is usually associated with opioid usage for analgesia 15 .…”
Section: Scalp Blockmentioning
confidence: 99%
“…A meta-analysis of ten studies published in a previous issue of the IJA concluded that scalp block might be useful at less than 6 h postcraniotomy with very low-quality evidence. [ 44 ] It is observed that a majority of scientific literature is focussed towards the immediate outcomes of surgery; nevertheless, the assessment of intermediate and long-term outcomes with nerve blocks is also important and needs further evaluation.…”
mentioning
confidence: 99%